THE EFFECTS OF SALES AND RECEIVABLE TURNOVER TOWARDS NET PROFIT: A STUDY ON BASIC AND CHEMICAL INDUSTRIAL SECTOR MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE FOR PERIOD OF 2012-2016 - Yanti; Maemunah, Mumun; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine how the effect of sales and receivable turnover on net income and the magnitude of the effect of sales and turnover of receivables on net income in manufacturing companies in the basic and chemical industry sectors that are listed on the Indonesia Stock Exchange. The method used in this research is quantitative method with descriptive and verification research approaches. The population in this study are basic and chemical industry manufacturing companies listed on the Indonesia Stock Exchange in 2012 until 2016 as many as 66 companies, and the sample in this study consisted of 15 basic and chemical industry manufacturing companies listed on the Indonesia Stock Exchange meets the specified criteria. Data analysis methods used are the classic assumption test, multiple regression analysis, coefficient of determination and hypothesis testing. The type of data used is secondary data, by collecting the annual financial statements of companies manufacturing basic and chemical industry sectors which are listed on the Indonesia Stock Exchange from 2012 to 2016.Based on the results of the t test shows the level of significance obtained from the variable sales of 0,000